Defining Abnormal Fetal Growth and Perinatal Risk: Population or Customized Standards? - Stock, Sarah J. (PLoS Med, 2017)
In January's Guest Editorial, Sarah Stock and Jenny Myers discuss approaches to fetal and neonatal growth assessment.